2019
DOI: 10.1177/2050640619834839
|View full text |Cite
|
Sign up to set email alerts
|

The revised Atlanta criteria more accurately reflect severity of post‐ERCP pancreatitis compared to the consensus criteria

Abstract: Background and objective: Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is the most prevalent complication after ERCP with an incidence of 3.5%. PEP severity is classified according to either the consensus criteria or the revised Atlanta criteria. In this international cohort study we investigated which classification is the strongest predictor of PEP-related mortality. Methods: We reviewed 13,384 consecutive ERCPs performed between 2012 and 2017 in eight hospitals. We gathered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
(54 reference statements)
0
21
0
7
Order By: Relevance
“…At the core of this system was the consequence of AEs in terms of admission to hospital and/or intensive care unit, the type of treatment applied, and death or permanent disability outcomes. This system is useful for research and comparison purposes but for some AEs, more specific classification systems are available: ▪ Pancreatitis: the revised Atlanta classification of severity [10] is a better predictor for PEP-related mortality than a system based on hospital duration as shown in a multicenter comparison with the 1991 consensus criteria (retrospective study of 387 patients with PEP) [22]. The determinant-based classification is accurate but has not been compared with alternatives in the setting of PEP [23,24] ▪ Cholangitis and cholecystitis: the revised Tokyo severity grading systems may offer more accurate predictive power than the generic alternatives; they are presented in a ▶ Table 1 Incidence, mortality and severity grading of the most common ERCP-related adverse events.…”
Section: Definitions and Epidemiologymentioning
confidence: 99%
“…At the core of this system was the consequence of AEs in terms of admission to hospital and/or intensive care unit, the type of treatment applied, and death or permanent disability outcomes. This system is useful for research and comparison purposes but for some AEs, more specific classification systems are available: ▪ Pancreatitis: the revised Atlanta classification of severity [10] is a better predictor for PEP-related mortality than a system based on hospital duration as shown in a multicenter comparison with the 1991 consensus criteria (retrospective study of 387 patients with PEP) [22]. The determinant-based classification is accurate but has not been compared with alternatives in the setting of PEP [23,24] ▪ Cholangitis and cholecystitis: the revised Tokyo severity grading systems may offer more accurate predictive power than the generic alternatives; they are presented in a ▶ Table 1 Incidence, mortality and severity grading of the most common ERCP-related adverse events.…”
Section: Definitions and Epidemiologymentioning
confidence: 99%
“…The limitation is the fact that it is not primarily developed to define PEP. For an assessment of the severity of PEP, it has been reported that the revised Atlanta classification is superior for predicting PEP mortality[6]. The frequency of PEP is reported to be 3% to 15%[7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These consensus criteria have been most commonly used in landmark trials on post-ERCP prevention, epidemiological studies and in ERCP guidelines. 35 However, duration of hospitalization is a key component of these criteria, which may be confounded by patient pain tolerance and physician practice, among other factors. The revised Atlanta classification of acute pancreatitis consensus definitions stratify pancreatitis severity based on the presence of local and systemic adverse events, including duration of organ failure, rather than duration of hospitalization.…”
Section: Discussionmentioning
confidence: 99%